2020
DOI: 10.3390/nu12123879
|View full text |Cite
|
Sign up to set email alerts
|

How Minority Parents Could Help Children Develop Healthy Eating Behaviors: Parent and Child Perspectives

Abstract: Minority children and children living in under-resourced households are at the greatest risk for obesity and diet-related disparities. Identifying effective strategies to reduce these risks is an important step in child obesity prevention. Parents influence the home environment and play a critical role in child obesity prevention. Eighteen parent–child dyads living in under-resourced Houston area communities participated in a mixed methods study (online surveys, telephone interviews). The purpose of the resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…Además, dentro de la población diana se incluirán tanto a padres y madres como a personal docente de los centros educativos seleccionados. Esta decisión está fundamentada por nuestro marco conceptual, teniendo en cuenta que los alumnos, pese a tener cierto grado de independencia, no son responsables de la elaboración ni de la elección de los alimentos que consumen a lo largo del día, y por lo tanto resulta crucial que la aplicación del programa sea transversal e involucre a dichos responsables para poder lograr el objetivo [20][21][22] .…”
Section: Metodología Población Y Grupo Dianaunclassified
See 1 more Smart Citation
“…Además, dentro de la población diana se incluirán tanto a padres y madres como a personal docente de los centros educativos seleccionados. Esta decisión está fundamentada por nuestro marco conceptual, teniendo en cuenta que los alumnos, pese a tener cierto grado de independencia, no son responsables de la elaboración ni de la elección de los alimentos que consumen a lo largo del día, y por lo tanto resulta crucial que la aplicación del programa sea transversal e involucre a dichos responsables para poder lograr el objetivo [20][21][22] .…”
Section: Metodología Población Y Grupo Dianaunclassified
“…En ausencia de cambios en las políticas a nivel poblacional, deben realizarse intervenciones específicas sobre alimentación enfocadas a los cuidadores de los infantes, ya que es en el entorno familiar en el que se establecen y promueven conductas beneficiosas para la salud a través del ejemplo y la provisión de alimentos saludables, además del apoyo para participar en conductas alimentarias saludables 20,22 .…”
Section: Introductionunclassified
“…Research conducted to date has shown that parents, teachers, peers, and health professionals play a critical role in shaping a child’s lifestyle. Creating an environment conducive to healthy habits within the home is one of the many ways parents can encourage healthy behaviors among their children [ 13 ]. Teachers can incorporate physical activity and healthy eating habits into the school curriculum, while peers can influence a child’s behavior through social norms and peer pressure [ 54 ].…”
Section: Introductionmentioning
confidence: 99%